PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PT INDAH KIAT PULP & PAPER TBK PERIODE 2013-2022 - Meida, Anna; Sutiman (Journal of Research and Publication Innovation, 2024)
This study aims to examine the effect of Current Ratio (CR) and Debt To Equity Ratio on Share Price at PT Indah Kiat Pulp & Paper Tbk for the period 2013-2022. The type of research used is quantitative research using associative methods. The population in this study were all financial statements of PT Indah Kiat Pulp and Paper Tbk listed on the BEI. While the sample used is the Balance Sheet and Income Statement at PT Indah Kiat Pulp & Paper Tbk for the period from 2013 - 2022. The data analysis method uses multiple linear regression tests, correlation coefficient, coefficient of determination, pasrial t test and simultaneous f test.  The results of the study showed that there was a partial influence (T test) Current Ratio (CR) on the share price of PT Indah Kiat Pulp & Paper Tbk. Proven by the value of TTest 4.411> Ttable 2.365 with a significant level of 0.003 <0.05. While Debt To Equity Ratio (DER) has no significant effect on Stock Price. Evidenced by the TTest value of 0.284 < 2.365 with a significant level of 0.784> 0.05. Simultaneously (F test) Current Ratio (CR) and Debt To Equity Ratio (DER) on Stock Price there is an influence. Proven by the Fcount value of 29.055> 4.26 with a significant level of 0.000 <0.05.